2017
DOI: 10.1001/jamainternmed.2017.0605
|View full text |Cite
|
Sign up to set email alerts
|

Initial Public Reporting of Quality at Veterans Affairs vs Non–Veterans Affairs Hospitals

Abstract: for their contributions to this project, which included data extraction review. No compensation was received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 4 publications
3
42
1
Order By: Relevance
“…Our findings differ somewhat from other recent studies comparing VA and non-VA inpatient care. 9,22 For example, in contrast to a study of Hospital Compare performance data from a similar timeframe, 9 we found that readmission rates were higher for AMI, heart failure, and pneumonia in VA hospitals than in non-VA hospitals; such discrepancies may be because the non-VA comparison hospitals in our analysis are a subset of all U.S. hospitals that have been matched to more closely mirror the characteristics of VA hospitals, rather than a broader set of non-VA hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings differ somewhat from other recent studies comparing VA and non-VA inpatient care. 9,22 For example, in contrast to a study of Hospital Compare performance data from a similar timeframe, 9 we found that readmission rates were higher for AMI, heart failure, and pneumonia in VA hospitals than in non-VA hospitals; such discrepancies may be because the non-VA comparison hospitals in our analysis are a subset of all U.S. hospitals that have been matched to more closely mirror the characteristics of VA hospitals, rather than a broader set of non-VA hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, a recent study comparing commonly reported measures in VA and non-VA hospitals found that VA hospitals performed better or the same as non-VA hospitals with regard to patient safety, better than non-VA hospitals with regard to mortality and readmissions, and showed mixed performance compared to non-VA hospitals on measures of patient care experiences and behavioral health. 9 Building upon this prior work, we assessed quality of both outpatient and inpatient care in VA settings using nationally recognized performance measures from 2013 to 2014. We examined VA's performance at the national level, assessed variation in performance across VA facilities, and compared performance in VA and non-VA settings in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Most notably, inpatient care for myocardial infarction, heart failure, or chronic obstructive pulmonary disorder is associated with lower mortality rates in VA compared with non-VA hospitals. 15,16 To date, little is known about variation in veterans' outcomes across different dialysis settings and financial arrangements. Recent analyses have shown that survival among veterans with CKD differs by VA and non-VA providers, 4,[17][18][19] which may be a function of differences in patient characteristics, quality of care, and care coordination across settings.…”
mentioning
confidence: 99%
“…The VHA hospitals also exhibited better readmission and mortality rates. 28 Any discovery made in the Department of Veterans Affairs is ultimately shared with the entire world and benefits all of humanity.…”
Section: Dr Erik Langhoff James J Peters Va Medical Centermentioning
confidence: 99%